Koruma tedbirleri nedeniyle tazminat - Güngör, Esra (My University, 2019)
Tez çalışmamızda temel hak ve özgürlükleri yakından ilgilendiren koruma tedbirleri nedeniyle tazminat konusu incelenmiştir. Koruma tedbirleri nedeniyle tazminatın tarihi geçmişine bakılarak koruma tedbirlerinin ve tazminat kavramlarının ortaya çıkış felsefesine değinilmiştir. Kişiye tazminat hakkı veren koruma tedbirlerinin kavramsal olarak neyi ifade ettiğine, sınıflandırılmasına, özelliklerine ilişkin hususlarla koruma tedbirlerine başvurmak için gereken ön koşullara yer verilmiştir. Belirtmiş olduğumuz bu hususlar koruma tedbirleri nedeniyle tazminata hükmedilirken belirleyici olan hususlardır. Bu kapsamda ayrıca koruma tedbirleri nedeniyle tazminatın hukuki esasına yönelik öğretide ortaya konmuş olan bir takım teorilere yer verilmiştir.Tüm bu açıklamalar doğrultusunda 5271 sayılı Ceza Muhakemesi Kanununda sayılan tazminat nedenleri Yargıtay ve Avrupa İnsan Hakları Mahkemesi Kararları ışığında ayrıntılı olarak ele alınmıştır. Kanundaki eksikliklere ve uygulamadaki sorunlara öğretide getirilen çözüm önerileri ışığında yer verilerek koruma tedbirleri nedeniyle tazminat kavramının hukuken yeterli olması için yapılması gereken düzenlemelere de yer verilmiştir. Nihayetinde koruma tedbirleri nedeniyle tazminata başvuru için gerekli olan usul ve esasa yönelik şartlar ele alınmış olup, tazminata engel olan haller ve tazminatın geri alınmasını gerektiren hususlara da yer verilerek çalışmamıza son verilmiştir.

In our thesis study, the subject of indemnification arising from the protection measures, which is closely related to the fundamental rights and freedoms, has been examined. Concepts of the inception philosophy of the protection measures and indemnification have been mentioned, considering the historical background of indemnification arising from protection measures. The significance and classification of the protection measures that vest a person the right of indemnification, matters regarding to the features of the protection measures and the prerequisites required to apply for the protection measures have been included. These abovementioned factors are the determinant ones in the indemnification conviction arising from the protection measures. In addition, within this context, a number of theories suggested in the doctrine regarding the legal basis of indemnification arising from the protection measures have been involved.In line with all these explanations, the reasons for the indemnification set forth under the the Code of Criminal Procedure No. 5271 have been discussed in detail, in the light of the Supreme Court and the European Court of Human Rights decisions. The necessary regulations need to be implemented in order the concept of indemnificationarising from the protection measures to be legally sufficient have also been included by means of examining the deficiencies in the legislation and the problems in the practice, in the light of the suggestions offered in the doctrine. In conclusion, the thesis has been finalized by discussing the conditions regarding the procedure and principle required in order to apply for the indemnification arising from the protection measures and including the obstacles for indemnification and the conditions requiring the indemnification to be revoked.
Keywords: Hukuk; Indemnification Arising From the Protection Measures; Indemnification Obstacles; Kamu hukuku; Koruma Tedbirleri; Koruma Tedbirleri Nedeniyle Tazminat; Law; Protection Measures; Public law; Revoke of Indemnification; Tazminat Engelleri Fundamental Rights and Freedoms; Tazminatın Geri Alınması; Temel Hak ve Özgürlükler